2016
DOI: 10.1016/j.molcel.2016.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of DHHC20-Mediated EGFR Palmitoylation Creates a Dependence on EGFR Signaling

Abstract: SUMMARY Inappropriate activation of the receptor tyrosine kinase EGFR contributes to a variety of human malignancies. Here we show a mechanism to induce vulnerability to an existing first line treatment for EGFR driven cancers. We find that inhibiting the palmitoyltransferase DHHC20 creates a dependence on EGFR signaling for cancer cell survival. The loss of palmitoylation increases sustained EGFR signal activation and sensitizes cells to EGFR tyrosine kinase inhibition. Our work shows that the reversible modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
167
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 168 publications
(194 citation statements)
references
References 20 publications
11
167
0
1
Order By: Relevance
“…DHHC20 is also known to be expressed in MDA-MB-231 cells, where it palmitoylates EGFR and attenuates EGFR signaling (28). We asked whether loss of DHHC20 would affect protein localization.…”
Section: Resultsmentioning
confidence: 99%
“…DHHC20 is also known to be expressed in MDA-MB-231 cells, where it palmitoylates EGFR and attenuates EGFR signaling (28). We asked whether loss of DHHC20 would affect protein localization.…”
Section: Resultsmentioning
confidence: 99%
“…1A) (16). Although inhibition of DHHC20 by shRNA leads to an increase in sensitivity to gefitinib-induced cell death, it is still unclear if this effect was directly mediated by inhibiting EGFR palmitoylation or if it is the effect of another unknown target of DHHC20.…”
Section: Resultsmentioning
confidence: 99%
“…Although inhibition of DHHC20 by shRNA leads to an increase in sensitivity to gefitinib-induced cell death, it is still unclear if this effect was directly mediated by inhibiting EGFR palmitoylation or if it is the effect of another unknown target of DHHC20. We previously showed that EGFR is palmitoylated on the C-terminal tail and that mutating one of the palmitoylated cysteine residues 1025 to alanine is sufficient to reduce receptor palmitoylation, induce receptor autophosphorylation, adaptor binding and downstream signaling to AKT and ERK when transiently expressed in NIH3T3 cells (16). To test if blocking EGFR palmitoylation directly increases gefitinib sensitivity of human cancer cells, we developed a conditional system for expressing wild type EGFR (EGFR WT ) or palmitoylation defective EGFR with cysteine 1025 mutated to alanine (EGFR C1025A ) in MDA-MB-231 cells with a tetracycline-inducible promoter.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…DHHC proteins and their substrates play important roles in tumorigenesis (13,14). Palmitoylation of H-and N-Ras facilitates Ras localization to the plasma membrane and is required for protein activity (15,16), and inhibiting ZDHHC20 palmitoyltransferase leads to the dependence of cancer cells on EGF receptor signaling for survival (17).…”
Section: Introductionmentioning
confidence: 99%